Designing a hotel website: An empirical analysis for a classic destination using a conjoint experiment - R. Huertas-Garcia; J. C. Gázquez-Abad; S. Forgas-Coll; A. Casas-Romeo (South African Journal of Business Management, 2014)
Internet has become one of the most important channels for the promotion and sale of services related to tourism. As a result, producers and distributors alike are keen to resolve the question as to which factors will determine website choice by internet browsers. In this paper we develop an experiment to determine the factors that need to be taken into consideration when designing a website for a mature, familiar tourist destination. To this end, the basic factors shaping the architecture of a website are theoretically described and, based on the results of a conjoint experiment, the main factors influencing a website for a classic destination are extracted. Our results suggest that a website that includes objective information (e.g., price, activities of interest, number of rooms) and multiple photos has a positive influence on customer perceptions. The paper also makes an important methodological contribution, as it proposes a new design for calculating the weight of the factors, interactions of two factors and the factors squared.
Keywords: 650